The Church of Scotland's Parochial Extension Scheme and the Scottish Disruption - Chambers, Don (A journal of church and state, 1974)
Don Chambers; The Church of Scotland's Parochial Extension Scheme and the Scottish Disruption, Journal of Church and State, Volume 16, Issue 2, 1 March 1974, Pa